2021
DOI: 10.3390/nu13082564
|View full text |Cite
|
Sign up to set email alerts
|

Combining the Anticancer and Immunomodulatory Effects of Astragalus and Shiitake as an Integrated Therapeutic Approach

Abstract: Astragalus root (Huang Qi) and Shiitake mushrooms (Lentinus edodes) are both considered medicinal foods and are frequently used in traditional Chinese medicine due to their anticancer and immunomodulating properties. Here, the scientific literatures describing evidence for the anticancer and immunogenic properties of Shiitake and Astragalus were reviewed. Based on our experimental data, the potential to develop medicinal food with combined bioactivities was assessed using Shiitake mushrooms grown over Astragal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 102 publications
0
16
0
Order By: Relevance
“…synergistically in cancer cell signaling pathways [11] and that mushroom active compounds combined with conventional therapies [11] can improve the outcome of and tolerance to invasive treatments [12][13][14], this work aims to provide an overview of the role of mushrooms as an adjuvant in conventional therapies, that emerged in clinical studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…synergistically in cancer cell signaling pathways [11] and that mushroom active compounds combined with conventional therapies [11] can improve the outcome of and tolerance to invasive treatments [12][13][14], this work aims to provide an overview of the role of mushrooms as an adjuvant in conventional therapies, that emerged in clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…The promising effects of mushrooms have been demonstrated on mushroom isolated compounds, and the role of the entire mushroom substances has been underestimated. Considering that it has been suggested that all active compounds of mushrooms can act synergistically in cancer cell signaling pathways [11] and that mushroom active compounds combined with conventional therapies [11] can improve the outcome of and tolerance to invasive treatments [12][13][14], this work aims to provide an overview of the role of mushrooms as an adjuvant in conventional therapies, that emerged in clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Bioactive substances of astragalus include polysaccharides, triterpene glycosides, and flavonoids. Flavonoids are a class of polyphenolic secondary metabolites, which have been demonstrated to have the effects of immune enhancement, antioxidant, antihypertensive, antiaging, antifatigue, and anti-inflammatory activities, thus reduced energy consumption and provided energy support, which may be related to the weight gain of rats [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dried sample powders of A. membranaceus , Shiitake ( L. edodes ), HAS 5% (HAS-A) and HAS 20% (HAS-B) were provided by Shanxi Yulongxiang Agricultural Development Co. Ltd., China. The cultivation and preparation conditions were described in our earlier study [ 23 ]. The enzymes Alcalase and VinoTaste ® Pro were obtained as gift samples from Novozymes Pty Ltd., Sydney, Australia.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the above facts, our industry collaborator (Shanxi Yulongxiang Agricultural Development Co. Ltd., Datong, China) developed a novel mushroom by growing Shiitake in the substrate beds supplemented with the roots of Astragalus membranaceus , a well-known edible herbal medicine with anti-cancer and immunomodulatory effects [ 18 , 19 , 20 , 21 , 22 ], and named it as Hengshan Astragalus Shiitake (HAS). Two different varieties of HAS, HAS-5% (HAS-A, growing on substrate with 5% A. membranaceus supplementation) and HAS-20% (HAS-B, growing on substrate with 20% A. membranaceus supplementation), were used in this study, which were proven to contain some bio-transformed components of Astragalus , determined by global metabolome analysis in our previous study [ 23 ]. According to the literature, one of the major active components providing anti-cancer effects in both Astragalus and Shiitake is polysaccharide [ 5 , 6 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%